'Beautiful' unconventional synthesis and processing technologies of superconductors and some other materials - Petre Badica, Adrian Crisan, Gheorghe Aldica, Kazuhiro Endo, Hanna Borodianska, Kazumasa Togano, Satoshi Awaji, Kazuo Watanabe, Yoshio Sakka and Oleg Vasylkiv (Science and Technology of Advanced Materials, 2011)
Superconducting materials have contributed significantly to the development of modern materials science and engineering. Specific technological solutions for their synthesis and processing helped in understanding the principles and approaches to the design, fabrication and application of many other materials. In this review, we explore the bidirectional relationship between the general and particular synthesis concepts. The analysis is mostly based on our studies where some unconventional technologies were applied to different superconductors and some other materials. These technologies include spray-frozen freeze-drying, fast pyrolysis, field-assisted sintering (or spark plasma sintering), nanoblasting, processing in high magnetic fields, methods of control of supersaturation and migration during film growth, and mechanical treatments of composite wires. The analysis provides future research directions and some key elements to define the concept of 'beautiful' technology in materials science. It also reconfirms the key position and importance of superconductors in the development of new materials and unconventional synthesis approaches.